Assessment of Patients Adherence to Oral Regimen of Drug-Resistant Tuberculosis among Iraqi Patients - Noor Alaa Jasim; Manal Khalid Abdulridha; Ahmed Asmar Mankhy; Ahmed Hadi Tarish (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
Background: Drug-resistant tuberculosis is an airborne chronic infectious disease that has evolved resistance to at least two anti-TB medications (isoniazid and rifampin). For the drug-resistant tuberculosis epidemic to be controlled, it is essential that patients be cured. However, therapeutic failure is often caused by patients who don't adhere to their prescribed regimen.